Ide Filosofis pada Tradisi Maulid Adat Bayan di Masyarakat Lombok Utara: Philosophical Ideas in the Maulid Tradition of Bayan Custom in North Lombok Society - Hifzurrohmi, Hifzurrohmi; Budiwati, Anisah (Jurnal Filsafat Indonesia, 2025)
The aim of this research is to discover and describe philosophical values ​​and ideas using Max Scheler’s perspective found in the Maulid Adat Bayan tradition, North Lombok. This tradition is a tradition that is still guarded and preserved by the Bayan Indigenous community as a commemoration of the birthday of the noble prophet Muhammad SAW. The lack of literacy and knowledge means that the public also lacks understanding of the traditional Mawlid tradition, which is limited to simply implementing customs and not understanding their philosophical values. This article is a qualitative research study library research. This article explores and examines the values ​​contained in the Maulid Adat Bayan tradition in depth from the perspective of Max Scheler’s value philosophy used. The research results obtained in this article can be concluded that Max Scheler’s hierarchy of values ​​includes pleasure, life, spirituality and the highest, namely religious. And the most dominant values ​​or philosophical ideas contained in this tradition include the value of pleasure which of course occupies the most dominant position because the aim of its implementation is a form of joy in the Muslim community welcoming the birthday of the Great Prophet Muhammad SAW, then after that there are religious values, spiritual values ​​and vital values ​​which are in the last position in the Traditional Maulid Tradition. The purpose of writing this article is to understand the public that the implementation of the traditional birthday tradition contains values, philosophical ideas and meanings that cannot be separated from our daily lives.